CuS/Graphene Nanocomposite as a Transparent Conducting Oxide and Pt-Free Counter Electrode for Dye-Sensitized Solar Cells. Issue 5 (1st January 2019) - Mohammadnezhad, Mahyar; Selopal, Gurpreet Singh; Alsayyari, Nasser; Akilimali, Rusoma; Navarro-Pardo, Fabiola; Wang, Zhiming M.; Stansfield, Barry; Zhao, Haiguang; Rosei, Federico
Abstract : We report a simple, low temperature and solution-processable approach to prepare a composite film of copper sulfide/graphene (CuS-G) as a transparent conducting oxide (TCO) and platinum (Pt)-free CE for Dye-Sensitized Solar Cells (DSSCs). We find that CuS with 3.3 vol% of graphene (CuS-3G) yields the highest power conversion efficiency (PCE) of 4.83%, which is about 12% higher than DSSCs based on CEs made of pristine CuS. After optimizing the graphene concentration, the PCE of the DSSC assembled with the optimized CuS-3G is comparable to that based on Pt CE. The similar performance of the CuS-3G CE compared with Pt CE is mainly attributed to the small series resistance and high electrocatalytic activity of the CuS-3G CE; this is confirmed by cyclic voltammetry and electrochemical impedance spectroscopy. These results indicate a straightforward methodology for the low cost and easy synthesis of an alternative CE in DSSCs.